Goldenhar Syndrome - Arash Ahmadzadeh; Ali Ahmadzadeh (Majalah-i ̒ilmī pizishkī-i jundī/shapūr)
Goldenhar syndrome (GS) or Oculo-Auriculo-Vertebral Syndrome is a rare disease characterized by craniofacial anomalies such as hypoplasia of the mandible and malar bone, microtia, and vertebral anomalies. GS is an etiologically heterogeneous disorder that may have a genetic basis in some cases. Here, a 3-month-old girl with GS is reported. She was brought for routine check-up. On physical examination, the unusual features were facial asymmetry, unilateral macrostomia, a preauricular tag low set ear, atresia of external ear canal and an epibulbar dermoid cyst at the left side. Brain-stem evoked response audiometry showed severe-profound conductive hearing loss on the left side. She has an older brother with the same problems. Congenital malformations in patient with GS are unilateral. Early detection and treatment of hearing loss is very important in the development of the patient.